Motywy polskie w twórczości krytycznoliterackiej Arriga Boito. Od Mickiewicza do Zaciśniętej pięści - Filonik, Apolonia (Colloquia Litteraria, 2023)
Arrigo Boito’s (1842–1918) relationship with poland has been studied extensively since 1963, when Walerian preisner published a monographic study of Boito and his connections to poland. In subsequent years, additional publications focusing on this artist with polish roots have appeared. The article on polish motifs in Boito’s critical and literary work summarizes the influence of polish literature, particularly the works of Adam Mickiewicz, on the Italian’s oeuvre. This article not only builds on the research of previous scholars but also offers new insights and observations.